Gaya Kepemimpinan Bupati terhadap Kinerja Aparat Birokrasi di Kabupaten Pangkep - Amrin, Amrin; Rahman, Rahman; Hasran, Hasran (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
This study aims to find out theoretically and empirically about the leadership style of the district head in relation to the performance of the bureaucratic apparatus, in the context of carrying out government, development and social tasks in Pangkep Regency. The results of the study show that the leadership of the Pangkep Regent in improving the performance of his bureaucratic apparatus can be assessed as good. This is based on information and answers from respondents on the leadership style shown by the Pangkep Regent, where aspects of the leadership style assessment include his capacity and capability in running a democratic government system, as well as the personality of the Pangkep Regent himself